Combined soil and foliar ZnSO4 application improves wheat grain Zn concentration and Zn fractions in a calcareous soil. (28th November 2019) - Zhao, Aiqing; Wang, Bini; Tian, Xiaohong; Yang, Xingbin
Abstract: Dietary zinc (Zn) deficiency is a common micronutrient deficiency in humans. Zinc fertilization has been proved to be an effective approach to improve grain Zn concentration in wheat and alleviate Zn deficiency in humans. To maximize the potential of Zn fertilization, it is necessary to select appropriate Zn fertilizer forms and application methods. Here, combined soil and foliar application of ZnSO4, rather than Zn‐EDTA, effectively increased grain Zn concentration in winter wheat ( Triticum aestivum L. cv. "Xiaoyan 22") grown in a calcareous soil. However, neither ZnSO4 nor Zn‐EDTA, when applied to the soil or the foliage alone, had any significant effect on grain Zn concentration. The fractions of Zn loosely bound to organic matter, carbonate‐bound Zn and manganese oxide‐bound Zn in the rhizosphere soil changed dynamically over the course of the wheat growth period, with the highest levels found at the jointing stage. The residual ZnSO4 fertilizer had a positive effect on grain Zn concentration in the subsequent wheat crop due to increased storage of phytic acid in wheat grains and high concentrations of Zn loosely bound to organic matter and carbonate‐bound Zn in the soil. In comparison, Zn‐EDTA applied to the soil only increased the exchangeable‐Zn fraction, and had little residual effect on any other Zn fraction. Repeated soil applications of Zn‐EDTA would be effective to improve grain Zn concentration in wheat plants in subsequent years. Highlights: Effects of Zn fertilization in a calcareous soil were tested by a 3‐year field experiment. Combined soil and foliar application of ZnSO4 improved grain Zn concentration in wheat. Foliar ZnSO4 or Zn‐EDTA application alone had no significant effects on grain Zn concentration. Soil ZnSO4 application had a long‐term positive effect on grain Zn concentration in the subsequent wheat crop.